A Case Study on the Use of Virtual Fencing to Intensively Graze Angus Heifers Using Moving Front and Back-Fences - Verdon, Megan; Horton, Brian; Rawnsley, Richard (Frontiers in Animal Science, 2021)
Virtual fencing contains and controls grazing cattle using sensory cues rather than physical fences. The technology comprises a neckband-mounted device that delivers an audio cue when the animal nears a virtual boundary that has been set via global positioning system, followed by an electrical stimulus if it walks beyond the boundary. Virtual fencing has successfully been used to intensively graze cattle using a simple virtual front-fence, but a more complex intensive grazing system comprising moving virtual front and back-fences has not been assessed. We studied the effectiveness of virtual fencing technology to contain groups of Angus heifers within grazing cells defined by semi-permanent electric side-fences and virtual front and back-fences, compared to groups of heifers contained in cells defined only by electric fencing. Four groups of 10 Angus heifers were randomly allocated to a ‘control’ (grazed with a conventional electric fences, n=2 groups) or ‘virtual fence’ treatment (grazed with virtual fences, n=2 groups). The groups of heifers grazed four adjacent experimental paddocks that were established using TechnoGrazing™ infrastructure. An estimated 9.5 kg pasture DM/heifer.day was offered in each of three 3-day allocations. Data collected include cues delivered by the neckbands, time beyond the virtual boundaries, pasture consumption and live weight changes. The virtual front and back-fences successfully contained one group of heifers in their grazing cell, but the second group of heifers spent an increasing amount of time in the exclusion zone during the second and third allocations and consequently received an increasing number of audio and electrical stimuli. There were no effects of electric or virtual-fence treatment on live weight change or pasture utilisation. We hypothesise that by grazing heifers in adjacent paddocks our experimental design produced a motivation for some heifers to cross the virtual boundary to regain close contact with familiar conspecifics. Despite this, valuable learnings were gained from this study and ought to be disseminated. Most notably, virtual fencing should not be used to manage cattle that have close visual contact to other mobs. We conclude that the successful application of virtual fencing technology needs to accommodate the natural behaviours of cattle.